Repair of Temporal Bone Encephalocele following Canal Wall Down Mastoidectomy. (21st September 2014) - Blioskas, Sarantis; Magras, Ioannis; Polyzoidis, Stavros; Kouskouras, Konstantinos; Psillas, Georgios; Dova, Stamatia; Markou, Konstantinos
Abstract : We report a rare case of a temporal bone encephalocele after a canal wall down mastoidectomy performed to treat chronic otitis media with cholesteatoma. The patient was treated successfully via an intracranial approach. An enhanced layer-by-layer repair of the encephalocele and skull base deficit was achieved from intradurally to extradurally, using temporalis fascia, nasal septum cartilage, and artificial dural graft. After a 22-month follow-up period the patient remains symptom free and no recurrence is noted.